Die Unieke van Johannes Calvyn (1509-1564) se ‘Philosophia Christiana’; hoe dit verder Uitgebou is en Vandag vernuwe kan word - van der Walt, B. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2010)
This article is a philosophical introduction into the Christian philosophy or rather the worldview of John Calvin (1509-1564), indicating briefly how it was further developed in the Reformed world (especially in the philosophy of Vollenhoven, Dooyeweerd, Stoker and their followers) and also how it could be applied today. The introductory section explains the method according to which Calvin’s thought will be analysed. It will employ the distinction between context (the cultural), direction (the religious) and structure (the ontological). The first main section gives a brief sketch of the cultural (socio-economic-political) context within which Calvin lived and worked. The second section investigates, in comparison with the general developments in Western thinking and in particular in comparison with contemporary currents, the religious direction, trend or normative perspective of Calvin’s worldview. In this section also his emphasis on the need for a continuous reformation is dealt with in more detail. The third main section contains a critical evaluation of the ontological type of philosophy underlying his writings. The following aspects are investigated: his idea about God, his creational ordinances, the cosmos, the human being, his philosophy of society, how he viewed the relationship between reason and faith, and finally what he had in mind with philosophia Christiana (a Christian philosophy). The last main section applies the insights gained in the proceeding sections as to how, in a contemporary secular context, members of reformed churches in South Africa should think and live in a genuinely Reformational way. The essay is concluded with a brief review and preview.